Corporate Social Responsibility and Community Empowerment in the Mining Sector: Post-Mining Closure and Sustainable Development in Gunung Pongkor, Indonesia - Teguh Iman Santoso; Cindy Pricillia Octavenda; Muhammad Nurwaskita Alamsyah (International Journal of Islamic Business and Management Review, 2025)
This study examines the impact of Corporate Social Responsibility (CSR) post-mine closure on community empowerment and economic resilience in post-mining communities around Gn. Pongkor, Indonesia. Using a qualitative phenomenological approach, primary data were collected through in-depth interviews with nine key informants, including local leaders, community members, and CSR officers, alongside document analysis and participant observation. Findings reveal that participatory CSR initiatives—such as vocational training, agricultural cooperatives, and environmental rehabilitation—enhance community empowerment by fostering collective ownership and institutional collaboration. However, challenges persist, including inconsistent program continuity, market access barriers, and environmental degradation. The research concludes that effective CSR requires long-term stakeholder engagement, localized governance, and alignment with global sustainability frameworks to ensure post-closure resilience. This study advances CSR theory by demonstrating how context-driven, community-led strategies can transform post-mining recovery, offering practical insights for policymakers and corporations in resource-dependent economies. Keywords: CSR Implementation, Community Empowerment, Mining Sector